2012
DOI: 10.1021/ie3009023
|View full text |Cite
|
Sign up to set email alerts
|

Selective Recovery of Precious Metals from Acidic Leach Liquor of Circuit Boards of Spent Mobile Phones Using Chemically Modified Persimmon Tannin Gel

Abstract: A tannin-based novel adsorbent, named "BTU-PT gel", was prepared by immobilizing bisthiourea (BTU) ligand on persimmon tannin (PT) extract. The adsorption behaviors of precious metal ions along with other coexisting base metal ions onto BTU-PT gel were studied by batch and continuous column methods. The gel exhibited remarkable selectivity for precious metal ions such as Au(III), Pd(II), and Pt(IV) over base metal ions such as Cu(II), Fe(III), Ni(II), and Zn(II) in 1−5 mol dm −3 hydrochloric acid. The adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(85 citation statements)
references
References 46 publications
2
81
0
2
Order By: Relevance
“…The peaks at 1247 and 1059 cm -1 are attributed to symmetrical and asymmetrical C-O-C stretching vibrations. 6 These peak positions are consistent with the reported literature. 6 After grafting DMTD, significant changes were observed.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The peaks at 1247 and 1059 cm -1 are attributed to symmetrical and asymmetrical C-O-C stretching vibrations. 6 These peak positions are consistent with the reported literature. 6 After grafting DMTD, significant changes were observed.…”
Section: Resultssupporting
confidence: 92%
“…6 These peak positions are consistent with the reported literature. 6 After grafting DMTD, significant changes were observed. The peak that corresponds to the O−H stretching vibration at 3423 cm -1 shifted to 3428 cm -1 , the band was broader, and the intensity was slightly weaker; these observations indicate that cross-linking occurred at the hydroxyl group.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…It was shown the that tannin gel could be successfully regenerated for up to 5 cycles of use. Finally, an industrial study was done using actual circuit board leach liquor and as indicated in the initial laboratory work, the BTU-PT tannin gel acted as a successful adsorbent for precious metals while not taking up base metals in solution [32]. Work done by Yurtsever and Sengil at Sakarya University in Turkey explored the use of a valonia tannin gel for the removal of silver ions from solution.…”
Section: Tannin Gel Adsorptionmentioning
confidence: 99%